First we need to find derivative

`dy/dt=-cos t+tsin t-1`

Here we've used product rule to differentiate `-tcos t.`

Now we insert `dy/dt` and `y` into the initial value problem.

`t(-cos t+tsin t-1)=-tcos t-t+t^2sin t`

`-tcos t+t^2sin t-t=-tcos t-t+t^2sin t`

Obviously, the left and the right sides are equal to each other meaning...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

First we need to find derivative

`dy/dt=-cos t+tsin t-1`

Here we've used product rule to differentiate `-tcos t.`

Now we insert `dy/dt` and `y` into the initial value problem.

`t(-cos t+tsin t-1)=-tcos t-t+t^2sin t`

`-tcos t+t^2sin t-t=-tcos t-t+t^2sin t`

Obviously, the left and the right sides are equal to each other meaning that the solution satisfies the differential equation. Now we only need to check the initial condition.

`y(pi)=-pi cos pi-pi=-pi(-1)+pi=pi-pi=0`

Therefore, `y=-tcos t-t` satisfies both the differential equation and the initial condition meaning it is the solution to our initial value problem.